THE EFFECT OF NON PERFORMING FINANCING ON FINANCING IN ISLAMIC BANK DKI FOR THE 2010-2018 PERIOD - Ratna Dumilah (International Journal of Education, Information Technology, and Others, 2019)
This study aims to determine the effect of Non Performing Financing on Financing at Bank DKI Syariah. The method used is explanatory research. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study of thevariable Non Performing Financing obtained an average value of 17.32 %%. The financing variable obtained an average value of 17.29 %%. Non Performing Financing has a negative and significant effect on financing with a regression equation value of Y = 34,835 - 1,013X, and a correlation coefficient value of -0,741 or has a strong level of relationship with a determination value of 54.9%. Hypothesis testing obtained a significance of 0.022 <0.05.